Nilai etika lingkungan pada pertanian komunitas adat Sedulur Sikep Samin - Nandi Kurniawan; Budiaman Budiaman; A N Hidayah; Annisa Salsabilla (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
The life of the Samin indigenous community is an example of how humans and nature live in harmony. The people are successful farmers who are independent and prosperous. This study aims to find the environmental ethical values ​​of the ancestral teachings applied to the agricultural activities of the Samin community. The research used a qualitative approach with in-depth interviews, observations and document studies. Data were analyzed through a process of data condensation, data display, and drawing conclusions. The results of the study show that local wisdom in the Sedulur Sikep Samin indigenous community originates from the unwritten teachings of their ancestors. These teachings take the form of principles and values ​​that are passed down in each generation. The principles and values ​​of the teachings of the ancestors are used as life guidelines hat balances building the environment, social and economic systems. Agriculture is carried out through organic farming patterns with zero waste principles. The Samin people try to balance their life activities, both among living creatures and inanimate objects around them. The ancestral teachings on Samin agriculture are in accordance with eco-centrism ethics that ensure the sustainability of life for the next generation